PROMOSI PARIWISATA MELALUI DIGITAL DIPLOMACY: UPAYA INTERNASIONALISASI PARIWISATA DAERAH - Faturachman Alputra Sudirman; Wa Ode Dina Sarma; Fera Tri Susilawaty (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2020)
In the context of regional autonomy, the Regional Government can engage in international activities to develop the region's potential. Through digital diplomacy, it is easy for local governments to promote their potential. This study aims to determine the Wakatobi local government's digital diplomacy in promoting regional tourism in the international world. The research method used in this research uses a qualitative approach with the number of informants as many as three people from the Tourism and Creative Economy Office of Wakatobi Regency. The findings in this study indicate that the regional Government of Wakatobi's digital diplomacy utilizes social media and websites in informing various local tourism activities and potential, while also involving non-state actors. They assist in the implementation of digital diplomacy